2012
DOI: 10.3168/jds.2011-4887
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of unsaturated fat or coconut oil with monensin in lactating dairy cows fed 12 times daily. I. Protozoal abundance, nutrient digestibility, and microbial protein flow to the omasum

Abstract: Monensin (tradename: Rumensin) should reduce the extent of amino acid deamination in the rumen, and supplemental fat should decrease protozoal abundance and intraruminal N recycling. Because animal-vegetable (AV) fat can be biohydrogenated in the rumen and decrease its effectiveness as an anti-protozoal agent, we included diets supplemented with coconut oil (CNO) to inhibit protozoa. In a 6 × 6 Latin square design with a 2 × 3 factorial arrangement of treatments, 6 rumen-cannulated cows were fed diets without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 59 publications
(104 reference statements)
8
35
1
Order By: Relevance
“…Another study from the same group reported a 0.59 log unit decrease in protozoal numbers when sheep were fed CO at a concentration of 56 g/kg DM, which is 1.5 times more than the amount used in our study. A similar supplementation rate (50 g/kg DM) to dairy cows, provoked a decrease of 1.05 log units in total protozoa, with a shift in the protozoal community towards Epidinium and Isotricha, whereas Entodinium and Dasytricha seemed more sensitive to CO (Reveneau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Another study from the same group reported a 0.59 log unit decrease in protozoal numbers when sheep were fed CO at a concentration of 56 g/kg DM, which is 1.5 times more than the amount used in our study. A similar supplementation rate (50 g/kg DM) to dairy cows, provoked a decrease of 1.05 log units in total protozoa, with a shift in the protozoal community towards Epidinium and Isotricha, whereas Entodinium and Dasytricha seemed more sensitive to CO (Reveneau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Omasal flow of FA, milk FA profile, and FA digestibility data were analyzed as a 6 × 6 Latin square using PROC MIXED of SAS (v9.1; SAS Institute Inc., Cary, NC) as described in the companion article (Reveneau et al, 2012). Treatment means were compared using 5 preplanned orthogonal contrasts, with 6 coefficients shown in brackets respectively for control, AV fat, CNO, control + R, AV fat + R, and CNO + R: 1) the main effect of R [1 1 1 −1 −1 −1], 2) the main effect of control versus fat (i.e., the average of AV fat and CNO) [−2 1 1 −2 1 1], 3) the main effect of the fat source (i.e., AV fat vs. CNO) [0 −1 1 0 −1 1], 4) the interaction between R and fat [−2 1 1 2 −1 −1], and 5) the interaction between R and the fat source [0 −1 1 0 1 −1].…”
Section: Discussionmentioning
confidence: 99%
“…Animals, treatments, and the experimental design were described in the companion article (Reveneau et al, 2012). Feed, omasal, and fecal samples were collected and analyzed as described previously, except for FA analysis, which was conducted with one of the procedures reviewed by Palmquist and Jenkins (2003) as modified by Mathew et al (2011).…”
Section: Feed and Fecal Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a significant shift in fermentation from acetate, butyrate, and isovalerate toward propionate and valerate has been reported with the addition of fat (37). Because propionate is an important hydrogen sink, propionate is expected to result in decreased methane production per unit of fermentable matter (33).…”
Section: Resultsmentioning
confidence: 99%